2007
DOI: 10.1016/j.brainres.2007.01.120
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase inhibitors affect brain potentials in amnestic mild cognitive impairment

Abstract: Amnestic mild cognitive impairment (MCI) is an isolated episodic memory disorder that hasa high likelihood of progressing to Alzheimer's disease. Auditory sensory cortical responses (P50, N100) have been shown to be increased in amplitude in MCI compared to older controls. We tested whether (1) cortical potentials to other sensory modalities (somatosensory and visual) were also affected in MCI and (2) cholinesterase inhibitors (ChEIs), one of the therapies used in this disorder, modulated sensory cortical pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Also, we have examined amplitude changes in this work rather than latency shifting. Some research has been done on cholinesterase modifying drugs regarding early somatosensory and visual ERPs in MCI subjects and found drugs effects concerning very early somatosensory ERPs (N20, P50) but no effects on early visual ERPs (N70, P100, N150) [40]. Our result concurs that later post-stimulus ERPs (visual and cognitive processing) do not seem to be affected by cholinesterase treatments to the extent of altering ERP assessment of clinical status.…”
Section: Discussionsupporting
confidence: 85%
“…Also, we have examined amplitude changes in this work rather than latency shifting. Some research has been done on cholinesterase modifying drugs regarding early somatosensory and visual ERPs in MCI subjects and found drugs effects concerning very early somatosensory ERPs (N20, P50) but no effects on early visual ERPs (N70, P100, N150) [40]. Our result concurs that later post-stimulus ERPs (visual and cognitive processing) do not seem to be affected by cholinesterase treatments to the extent of altering ERP assessment of clinical status.…”
Section: Discussionsupporting
confidence: 85%
“…The enhanced P50 response is well described in patients with AD and MCI (Green et al ., ). Another study compared amnestic MCI patients treated with cholinesterase inhibitors to untreated patients and found larger P50 amplitudes in untreated patients with MCI (Irimajiri et al ., ). Another interesting study compared the brain responses of healthy subjects with and without AD relatives (Boutros et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…P50 amplitude predicted progression from MCI to AD, and differentiated amnestic MCI subtype from MCI with other cognitive impairments beyond memory deficit [96, 97]. Several studies have found N200 and P300 abnormalities in MCI, with some results suggesting that amplitude or latency of N200 may have stronger value in discriminating MCI patients from normal control [98100].…”
Section: Erps In Mild Cognitive Impairment (Mci)mentioning
confidence: 99%